Spontaneous Bladder Rupture after Normal Vaginal Delivery: Description of a Rare Complication and Systematic Review of the Literature - Guglielmo Stabile; Francesco Cracco; Davide De Santo; Giulia Zinicola; Federico Romano; Nicolò De Manzini; Serena Scomersi; Giuseppe Ricci (Diagnostics, 2021)
Objective: To identify the possible causes of spontaneous bladder rupture after normal vaginal delivery and to propose a diagnostic and therapeutic algorithm. Material and Methods: MEDLINE (PubMed), Web of Science and Scopus databases were searched up to August 2020. Manuscripts considered were published from 1990 and only English articles were included. The research strategy adopted included the following terms: (bladder rupture) AND (spontaneous) AND (delivery). 103 studies were identified. Duplicates were found through an independent manual screening. Subsequently, two authors independently screened the full text of articles and excluded those not pertinent to the topic. Discrepancies were resolved by consensus. Finally, thirteen studies were included. Results: PRISMA guidelines were followed. For each study, fetal weight, catheterization during labor, parity, maternal age, occurrence time, previous abdominal or pelvic surgery, symptoms complained of, diagnostic methods, and treatment were considered. Median age was 26.0 (range 20–34 years); median presentation time was 3.0 days after delivery (range 1–20 days); and median newborn weight was 3227.0 g (range 2685–3600 g). Catheterization during labor was reported only in four of the thirteen cases (30.8%) identified. The symptoms most frequently complained of were abdominal pain and distension, fever, oliguria, haematuria and vomiting. Instrumental diagnosis was performed using X-rays in five cases and computerized tomography in six cases. Ultrasound was chosen in five cases as a first diagnostic tool. In two cases, cystography was performed. Treatment was always laparotomic repair of the visceral defect. Conclusion: Abdominal pain, increased creatinine and other signs of kidney failure on blood tests should lead to suspicion of this complication. Cystourethrography is regarded as a procedure of choice, but a first ultrasound approach is recommended. The main factor for the therapeutic choice is the intraperitoneal or extraperitoneal rupture of the bladder. Classical management for intraperitoneal rupture of the bladder is surgical repair and urinary rest.